Towards the Multidimensional Measurement of Library Performance - Laitinen, Markku Antero; Juntumaa, Jouni Henrik; Kirichenko, Svetlana (Qualitative and Quantitative Methods in Libraries; Vol 10 No 3 (2021): September issue 2021, 2021)
The User Experience Index (IUX) is a composite index aimed to measure the overall user experience of services supplied by a library. The user satisfaction is evaluated by calculating the sum of the selected attributes coming from the (scaled) responses to user surveys and weighted by the coefficients assigned by experts. The reason for using the composite index approach is to capture the aggregate effect of multiple factors influencing the overall user experience. The attributes of the IUX were derived from the responses to the National User Survey conducted in Finland over several years in the same format. Altogether seven attributes were selected. The weights of these attributes in relation to each other were defined in a library directors’ workshop. The proposed composite index allows the libraries to follow a long-term development of the selected attributes through a single number encompassing their aggregate effect. At the same time, analysis of the individual attributes of the composite index can reveal components of the user experience that require special attention.